2018
DOI: 10.1103/physrevc.97.054611
|View full text |Cite
|
Sign up to set email alerts
|

Connection between angle-dependent phase ambiguities and the uniqueness of the partial-wave decomposition

Abstract: Unconstrained partial-wave amplitudes, obtained at discrete energies from fits to complete sets of eight independent observables, may be used to reconstruct reaction amplitudes. These partial-wave amplitudes do not vary smoothly with energy and are in principle non-unique. We demonstrate how this behavior can be ascribed to the continuum ambiguity. Starting from the spinless scattering case, we show how an unknown overall phase, depending on energy and angle, mixes the structures seen in the associated partial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 21 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…New relationships were discovered [416,461]. Studies of the phase-ambiguity problem, associated with amplitude analyses, were conducted in collaboration with the Mainz, Bonn, and Zagreb groups [462,463]. These studies have more clearly defined the amplitude information that can be extracted from data with minimal input from reaction models.…”
Section: Recent Progress With the Juelich-bonn And Said Analysis Frameworkmentioning
confidence: 99%
“…New relationships were discovered [416,461]. Studies of the phase-ambiguity problem, associated with amplitude analyses, were conducted in collaboration with the Mainz, Bonn, and Zagreb groups [462,463]. These studies have more clearly defined the amplitude information that can be extracted from data with minimal input from reaction models.…”
Section: Recent Progress With the Juelich-bonn And Said Analysis Frameworkmentioning
confidence: 99%
“…From our earlier research [1] we know that the natural candidate for such an effect is the change of reaction amplitude phase. As the essential part of our AA/PWA model is the penalty factor P, and the possible change of phase is introduced via this factor, we shall put this factor under magnifying glass.…”
Section: B Analysis Of Phase Dependence Of Solmentioning
confidence: 99%
“…In ref. [1] it has been shown that without fixing the reaction-amplitude phase, many combinations of partial waves at neighbouring energies in single-energy single-channel partial wave analysis reproduce experimental data identically, but are discontinuous and disconnected. So, to obtain the continuous solution, the phase has to be fixed to some continuous value.…”
Section: Introductionmentioning
confidence: 99%
“…It is a general knowledge that as a direct consequence of continuum ambiguity the unconstrained partial-wave amplitudes obtained at discrete energies even from fits to complete sets of eight independent observables [14] which are required to uniquely reconstruct reaction amplitudes do not vary smoothly with energy, and are in principle nonunique [15]. In [1] it has been shown that for a complete set of pseudo-data this problem can be easily solved by simple phase rotations.…”
Section: Introductionmentioning
confidence: 99%